Family and household rituals of the peoples in Dagestan: a historiographical review - Ruslan I. Seferbekov (Кавказология, 2022)
Based on historical-comparative, typological, chronological, and systemic general scientific methods, the article gives a historiographical review of pre-revolutionary, Soviet and recent historical, and ethnographic sources, as well as literature on the family rituals of the peoples of Dagestan. In the Soviet and Russian ethnographic tradition, these rituals are usually attributed to the rituals of the life cycle - birth, reaching maturity, changing social status, marriage, death, and burial. Rites of the life cycle are a group of rites that mark the main stages in the life of each member of society. They have ethno-cultural significance, since they are directly related to local, in particular, ethnic identity and act as an important mechanism for the formation and preservation of the stability of traditional culture. According to the author, pre-revolutionary historiography, presented by Russian and local Russian-speaking authors, was descriptive. Under the influence of the Marxist-Leninist ideology and the class approach in describing the phenomena of culture and life, Soviet historiography, represented by metropolitan and local ethnographers, was engaged in fixing marriage, family, wedding, maternity and funeral rites and customs of relics of ancient forms of family and marriage, pre-monotheistic beliefs, and party functionaries - the fight against obsolete harmful remnants and introducing new rituals into socialist life - Komsomol and no alcohol weddings, etc. Both Soviet and post-Soviet authors, describing family rituals, focused on clarifying the traditional layer and new customs. The latest historiography of family rituals pays attention to the transformational processes in them under the influence of globalization, modernization, and urbanization. Giving the nomenclature of historians and ethnologists of modern, Soviet and modern times engaged in the study of wedding, maternity and funeral rites of the peoples of Dagestan, the author also conducts researchers of family life among other peoples of the Caucasus and Russia.